Periocular necrotizing fasciitis - Somani, Zaynab; Kim, Hyun Jun; Harrison, Andrew; Mokhtarzadeh, Ali (Frontiers in Ophthalmology, 2026)
Necrotizing fasciitis is a rapidly progressive infection commonly associated with group A Streptococci and other toxin-producing bacteria that leads to microvascular thrombosis, tissue ischemia, and fascial plane spread. Although the periorbital region’s rich vascularity and natural anatomic barriers help limit deep extension and systemic spread, periorbital necrotizing fasciitis (PNF) can cause septicemia, systemic toxicity, and death. Early diagnosis is critical but remains challenging; distinguishing PNF from inflammatory mimics such as Sweet’s syndrome is critical given their opposing interventions. Surgical debridement along with intravenous antibiotics remain the cornerstone of treatment. However, considering the significant morbidity from vision loss and disfigurement, the decision to pursue early surgical debridement versus conservative management remains an area of active debate. Emerging blood biomarkers may aid diagnosis, and adjunctive therapies, including hypochlorous irrigation, show promise in improving outcomes of PNF while minimizing treatment-associated morbidities. This mini-review synthesizes current treatment evidence for PNF, integrating findings from PNF-focused literature and studies of generalized-NF at other anatomical sites. While principles utilized in the treatment of generalized NF may be applicable to PNF, exact statistics may vary by anatomic site.